2017
DOI: 10.1038/s41467-017-01208-w
|View full text |Cite
|
Sign up to set email alerts
|

A mesoporous cationic thorium-organic framework that rapidly traps anionic persistent organic pollutants

Abstract: Many environmental pollutants inherently exist in their anionic forms and are therefore highly mobile in natural water systems. Cationic framework materials that can capture those pollutants are highly desirable but scarcely reported. Here we present a mesoporous cationic thorium-based MOF (SCU-8) containing channels with a large inner diameter of 2.2 nm and possessing a high surface area of 1360 m2 g−1. The anion-exchange properties of SCU-8 were explored with many anions including small oxo anions like ReO4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
206
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 318 publications
(210 citation statements)
references
References 83 publications
4
206
0
Order By: Relevance
“…N 2 adsorption/desorption isotherms of Ta‐MOF (a) and PVA/Ta‐MOF nanofibrous samples (b) are shown in Figure . The isotherms resemble type (IV) BET isotherms representing mesoporous structures for both samples . According to the results obtained from the BET technique, the surface areas for Ta‐MOF and PVA/Ta‐MOF nanofibrous samples are 2212 and 2549 m 2 /g, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…N 2 adsorption/desorption isotherms of Ta‐MOF (a) and PVA/Ta‐MOF nanofibrous samples (b) are shown in Figure . The isotherms resemble type (IV) BET isotherms representing mesoporous structures for both samples . According to the results obtained from the BET technique, the surface areas for Ta‐MOF and PVA/Ta‐MOF nanofibrous samples are 2212 and 2549 m 2 /g, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…According to the applications of thorium nanostructures in various fields, our research team previously succeeded in synthesizing thorium (IV) MOF by developing ultrasonic and reverse micelle methods . Results indicated that the final products was found to be thermally stable up to 354 °C, particle size distribution of 27 nm, and surface area of 2020 m 2 /g, showing the considerable improvement in product properties by these novel methods in comparison with other methods.…”
Section: Introductionmentioning
confidence: 98%
“…In view of the different charge and molecular size of dye molecules, ionic metal-organic framework materials have great development prospects in the enrichment of toxic dye molecules because of its electrostatic interaction. [26][27][28][29][30][31][32][33][34][35][36][37][38][39] Gao [27] 4 ] cluster and tetratopic bis(isophthalic acid) linker have attracted extensive attention because of their ion nature and tunable pore size as the linker length changes. Based on the above considerations, it is believed that the intrinsic nature of NOTT-210 with suitable pore size has great advantages in achieving faster and more efficient adsorption and separation for different sizes of dye molecules.…”
Section: Introductionmentioning
confidence: 99%